Q: Simplify 6x plus 6 plus 5x - 8.?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

6x-x+15-9= 6x-x=5x 15-9=6 5x+6=0 5x=-6 x=-1.2

x(x2+5x+6)

5x + 4 = 6x - 2Add 2 to each side of the equation:5x + 6 = 6xSubtract 5x from each side:6 = x

18 + 7x - 12 + 5x = ?18 - 12+ 7x - 5x = ?6 + 2x = ?

If we recall that (5 cows plus 1 cow) = 6 cows, it immediately becomes apparent that5x plus 1x = 6x.

Related questions

6x-x+15-9= 6x-x=5x 15-9=6 5x+6=0 5x=-6 x=-1.2

5x-6+3x+128x-6+128x+6

x(x2+5x+6)

It simplifies to: 12 -6x

5x + 4 = 6x - 2Add 2 to each side of the equation:5x + 6 = 6xSubtract 5x from each side:6 = x

6x + 5 = 0 (I'm assuming) 6x = -5x = -5/6

5x^2 + 6x + 9 + (?) = -x^2 +3x + 3 (?) = -5x^2 -6x - 9 -x^2 +3x + 3 = -6x^2 -3x -6 Ans: -6x squared +3x -6

6x2 + 5x - 6 is factored out to (2x + 3)(3x - 2).

18 + 7x - 12 + 5x = ?18 - 12+ 7x - 5x = ?6 + 2x = ?

If we recall that (5 cows plus 1 cow) = 6 cows, it immediately becomes apparent that5x plus 1x = 6x.

x = 0,1

6x - 9 - x = 6Combine like terms on the left side:5x - 9 = 6Add 9 to each side:5x = 15Divide each side by 5:x = 3By the time you simplify it, you've solved it.